2015
DOI: 10.1108/el-07-2013-0130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and analysis of research data services in university libraries

Abstract: Purpose – This paper aims to find the current situation of research data services by academic libraries and summarize some strategies for university libraries to reference. Recent years have seen an increasing number of university libraries extended their traditional roles and provided research data services. Design/methodology/approach – This paper selected 87 libraries of the top 100 universities listed in the World’s Best Universities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 6 publications
2
41
0
2
Order By: Relevance
“…They may require assistance with activities such as creating metadata, locating datasets, and finding appropriate places to store their data (Aydinoglu, Suomela, & Malone, 2014;Enke et al, 2012;Kratz & Strasser, 2015;Schmidt, Gemeinholzer, & Treloar, 2016;Specht et al, 2015;Tenopir et al, 2011Tenopir et al, , 2015a. Earlier surveys of researchers suggest roles for research libraries in providing support for research data management, an extension of the library's traditional role in providing research and reference services (Si et al, 2015;Tenopir et al, 2012Tenopir et al, , 2015bVlaeminck, 2013).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They may require assistance with activities such as creating metadata, locating datasets, and finding appropriate places to store their data (Aydinoglu, Suomela, & Malone, 2014;Enke et al, 2012;Kratz & Strasser, 2015;Schmidt, Gemeinholzer, & Treloar, 2016;Specht et al, 2015;Tenopir et al, 2011Tenopir et al, , 2015a. Earlier surveys of researchers suggest roles for research libraries in providing support for research data management, an extension of the library's traditional role in providing research and reference services (Si et al, 2015;Tenopir et al, 2012Tenopir et al, , 2015bVlaeminck, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Libraries vary in how well they are able to support RDS and what range of services they offer (Corrall, Kennan, & Afzal, 2013;Cox & Pinfield, 2014;Si et al, 2015). Rittel and Weber (1973) describe a complex societal problem that is difficult to solve due to a number of factors.…”
Section: Related Workmentioning
confidence: 99%
“…A similar 2013 study across Australia, New Zealand, Ireland, and the United Kingdom revealed that the majority of the RDM service types they examined were currently available or planned at over half of the libraries included in the study (Corrall, Kennan, & Afzal, 2013). Of 87 top worldwide research universities evaluated by Si, Xing, Zhuang, Hua, and Zhou (2015), 50 offered research data services. The Virginia Commonwealth University has created a new position of Director of Research Data Management (Henderson & Knott, 2015), and Oregon State University now offers a credit-bearing graduate course in Research Data Management (Whitmire, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent international studies of research data services have identified a range of issues associated with these developments (Corrall, Kennan, & Afzal, 2013;Si, Xing, Zhuang, Hua, & Zhou, 2015). LIS have a key role in engaging and contributing to different stages in the research lifecycle and there are also critical implications for LIS education.…”
Section: Implications For Library and Information Servicesmentioning
confidence: 99%